2014
DOI: 10.1007/s13402-014-0187-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel CDC73 gene mutation in an Italian family with hyperparathyroidism-jaw tumour (HPT-JT) syndrome

Abstract: We report a novel mutation in the CDC73 gene that may underlie HPT-JT syndrome. This mutation appears to affect the C-terminal moiety of the encoded protein, which is thought to interact with other protein partners. The identification of these partners may be instrumental for our understanding of the CDC73-associated phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 17 publications
2
41
0
Order By: Relevance
“…All patients underwent parathyroidectomy (PTx) and followed-up at the University of Pisa (n = 28), Bologna (n = 4), IRCCS Casa Sollievo della Sofferenza Hospital San Giovanni Rotondo (n = 3). Eight cases of PC have been already published (Cetani et al 2013, Chiofalo et al 2014, Muscarella et al 2018.…”
Section: Patientsmentioning
confidence: 99%
“…All patients underwent parathyroidectomy (PTx) and followed-up at the University of Pisa (n = 28), Bologna (n = 4), IRCCS Casa Sollievo della Sofferenza Hospital San Giovanni Rotondo (n = 3). Eight cases of PC have been already published (Cetani et al 2013, Chiofalo et al 2014, Muscarella et al 2018.…”
Section: Patientsmentioning
confidence: 99%
“…Similarly, invasion and negative staining of parafibromin (Figure 2A) can be seen in SaPC cases. Recent studies showed that germline CDC73 mutation is closely related to HPT-JT syndrome and other variant phenotypes of sporadic PC (58,59). There might be a connection between germline CDC73 mutation and SaPC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous papers report novel mutations of deletions type in c.191-192 delT, [27] and (c.1379delT/p.L460Lfs*18). [28] While novel deletion of exons 4 to 10 of CDC73 was detected in another study. [29]…”
Section: Discussionmentioning
confidence: 99%